A Stackelberg Game Approach to Find Optimal Location and Pricing for Network of Charging Stations - Adil, Muhammad; Parvez Mahmud, M A; Kouzani, Abbas Z; Yang Khoo, Sui (2023 IEEE IAS Global Conference on Emerging Technologies (GlobConET), 2023)
This article proposes a Stackelberg game model for determining the optimal pricing and placement of electric vehicle charging stations. The model is based on a bi-level optimization technique that considers a follower problem for optimizing the profit of each charging station (CS) and a leader problem for optimizing the overall profit for a network of charging stations. The follower problem considers the pricing, energy sold, energy demand, energy cost, and station cost, subject to a constraint on the maximum distance from the station. The leader problem aims to maximize the overall profit of all stations, subject to charging allocation and distance constraints. The proposed approach uses Bender's decomposition algorithm to solve the profit maximization problem, where the pricing determines the charging allocation and resulting profit. The simulation results demonstrate the effectiveness of the proposed approach in maximizing the gain for the charging station network.